Inteligencia emocional y logro académico en los alumnos de educación secundaria de una institución educativa pública del Callao - Palacios Cangahuala, Vladimir Valerio (2010)
The present investigation has the intention of demonstrating the existing relation between the emotional intelligence and the academic achievement in the pupils of the fifth degree of secondary education of an educational institution of the district of the Callao. Correlacional used the descriptive design. The study was realized in a sample of 82 students of both kinds; with a sampling not probability. The was applied the inventory of BarOnʼs Emotional Quotient. The results indicate that a significant relation exists between emotional intelligence and academic achievement; likewise the levels of Emotional Intelligence indicate that 69.5% presents an emotional good capacity and 24.4% for improving. In addition, in relation to academic achievement one found that 37.8% presents a low level.